Penerapan Digitalisasi UMKM melalui E-Commerce dan Portal Informasi sebagai Strategi Pemasaran Produk ATBM Desa Cepagan - Ari Muhardono; Dina Amalia Mahmudah; Tsamara Tsamara; Muhammad Baqo (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
This research is a research and development research that aims to design UMKMdigitization, which is to help SMEs ATBM in Cepagan Village increase marketing reachthrough E-Commerce and Information Portals. The System Development method used is thePrototype Method using an approach to make a design quickly and gradually which includesrequirements analysis, building prototyping, evaluating prototyping, coding the system,testing the system, and evaluating the system. The results of this research are theimplementation of the digitization of MSMEs which includes the creation of E-Commerce,Information Portal Websites, QRIS Digital Payment Methods, and Application of SearchEngine Optimization. With the existence of E-Commerce, it can help MSMEs in reaching awider market and increasing product sales turnover, the information portal website for theATBM Weaving Village in Cepagan Village is used as a medium of information about theactivities of the ATBM Weaving Village in Cepagan Village with the aim of reviving the imageand existence of Cepagan Village. known as the "Kampung Tenun" Cepagan Village so that itis known to the wider community and has proven to be effective in increasing website trafficso that the potential for purchases is higher